Menyeimbangkan Pertumbuhan dan Keberlanjutan: Bagaimana Pengelolaan Hutan, Desentralisasi Fiskal, dan Ekspansi Ekonomi Membentuk Kualitas Lingkungan di Indonesia - Ginanjar, Rah Adi Fahmi; Sutjipto, Hady; Suharto, Umayatu Suiroh; Suska, Suska; Zaki, Mohammad; Sardjasasmita, Agi (Jurnal Riset Ilmu Ekonomi, 2025)
This study examines how forest area, fiscal decentralisation, and sectoral economic growth affect environmental quality across Indonesian provinces. Forests are categorised into conservation, protected, and production areas. Fiscal decentralisation is analysed through natural resource revenue-sharing and local government environmental expenditures, while economic activity is segmented into the primary, secondary, and tertiary sectors. The analysis uses a dynamic panel dataset of 33 provinces from 2017 to 2022. To address potential endogeneity, the study employs a multi-stage estimation strategy, starting with Pooled OLS and Fixed Effects models, followed by the Durbin-Wu Hausman test to justify the use of a dynamic Generalised Method of Moments (GMM) framework, with System-GMM selected as the final estimator. The results indicate that natural resource revenue-sharing has a positive effect on environmental quality. However, economic growth across all sectors negatively impacts environmental outcomes, while environmental protection expenditure shows no significant effect. These findings emphasize the need to adjust decentralised fiscal policies to focus more on ecological outcomes and steer more sustainable regional development.